PENGABDIAN MASYARAKAT EDUKASI PENINGKATAN DISCHARGE PLANNING DI RUANG RAWAT INAP RUMAH SAKIT DEWI SRI KARAWANG - Asih, Okti Rahayu; Sugihartati, Nining; Sumitro, Sumitro; Suminar, Ami Siti; Novita, Debi (LP2M STP Mataram, 2024)
Discharge planning is a series of discharge planning processes that can provide information to patients and their families regarding things that need to be prepared and carried out regarding their illness. The patient's readiness to face discharge is one of the determining factors in the success of the treatment given at the hospital. Implementation of discharge planning that is not yet optimal can affect the quality of hospital services and the susceptibility of patients to recurrence. In the process, the role of the nurse is very important, therefore good and targeted communication is needed that can be understood by the patient and family. The aim of implementing this activity is to increase nurses' understanding in providing discharge planning to patients starting from the time the patient enters the hospital until the patient goes home. This activity is also expected to increase patient knowledge about treating their illness independently through education provided by nurses. The implementation method regarding treatment according to the patient's condition and disease uses educational media using infocus projector